Analysis of LDLR variants from homozygous FH patients carrying multiple mutations in the LDLR gene. (August 2017) - Jiang, Long; Benito-Vicente, Asier; Tang, Ling; Etxebarria, Aitor; Cui, Wei; Uribe, Kepa B.; Pan, Xiao-Dong; Ostolaza, Helena; Yang, Shi-Wei; Zhou, Yu-Jie; Martin, Cesar; Wang, Lu-Ya
Abstract: Background and aims: Familial hypercholesterolemia (FH) is an autosomal dominant disease with widespread global prevalence that partially accounts for the high prevalence of premature coronary heart disease. Although the majority of research on FH has focused on single heterozygous LDLR mutations, there have been limited reports of double LDLR mutations on the same chromosome. The aim of this study was to gain insight into the clinical consequences of the presence of multiple mutations in the LDLR gene. Methods: DNA from two clinical homozygous FH patients and their relatives was analysed using targeted exome sequencing and DNA resequencing. Functional characterization of novel variants was performed by Western blot, flow cytometry and confocal microscopy. Results: Proband 1 carried p.Q12X, NTDA (p.N276T and c.892delA) mutations in LDLR, and Proband 2 carried c.971delG, GSDN (p.G77S + D601N). Results showed that p.Q12X, c.892delA, and c.971delG are non-functional LDLR variants. Conversely, N276T and G77S are non-pathogenic variants. Interestingly, while D601N alone only slightly diminishes LDLR activity, its co-presence with the non pathogenic p.G77S mutation results in a more strongly pathogenic variant with LDLR activity reduced by 40%. One of the double mutants, NTDA, is as non functional as c.892delA alone. The other double mutant, GSDN, is more severe than either of the component single mutants. Conclusions: An early gene screening and laboratory functional verification of LDLR activity is of vital importance to enable a definite FH diagnosis. Functional verification is also necessary for prenatal and postnatal care in patients with FH. Highlights: Target exome sequencing found two HoFH children with uncommon double mutations on the same LDLR allele. Functional studies of double mutations showed different effect. An early gene screening and laboratory functional verification is important for prenatal and postnatal care.